Salespeople’s Customer Orientation and Customer Satisfaction: An SDL Perspective - Hayat Yusuf; Ardiansyah Goeliling; Astil; Syahra (Journal of Business & Banking, 2025)
This study aims to examine the influence of service quality and salespeople’s customer orientation on perceived value and customer satisfaction, as well as the mediating role of perceived value and the moderating role of brand image in the relationship between perceived value and customer satisfaction. This research was conducted on bank credit customers in Kendari City using a quantitative approach with an explanatory research design. Data were collected through a survey using a structured questionnaire distributed to 340 respondents. The data were analyzed using Structural Equation Modeling to test the diresct, indirect, and moderation effects in the proposed research model. The results show that service quality and salespeople’s customer orientation have positive effects on perceived value and customer satisfaction. Perceived value also has a positive effect on customer satisfaction, indicating that customers tend to be more satisfied when they perceive that bank credit services provide benefits that are worth the cost, time, effort, and risk involved. In addition, perceived value mediates the relationship between service quality and customer satisfaction, as well as the relationship between salespeople’s customer orientation and customer satisfaction. The findings also confirm that brand image strengthens the effect of perceived value on customer satisfaction.